Effect of Return on Assets, Current Ratio and Degree of Leverage on Debt To Equity Ratio Mixed Private Banking Sector Listed On The Indonesia Stock Exchange 2016-2020 - Hasanudin Hasanudin (International Journal of Artificial Intelligence Research, 2022)
The objective of this study is to examine the impact of profitability, liquidity, and business risk on the capital structure of private mixed banks listed on the Indonesia Stock Exchange (IDX). The population of this study consists of all banks registered on the Indonesia Stock Exchange between 2016 and 2020. Purposive sampling was used to determine the sample for this study, which consisted of 25 Private Banks. Using the website www.idx.co.id as a documentation source, secondary data was used as the data source. Using the Eviews ten application, a panel data regression analysis is employed as the analytical method. The results indicate that profitability, as measured by return on assets, has a positive and statistically significant effect on capital structure (DER). In contrast, liquidity, as measured by current assets, has a negative and statistically significant result. on capital structure (DER), whereas business risk, as approximated by the degree of operating leverage (DOL), has no meaningful impact on capital structure (DER).